(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
The Ogam (Modern Irish: Ogham) script is a peculiar writing system devised to write the Primitive Irish language, i.e. the precursor of Old Irish. This script which in its core consists of 20 letters that are made up of 1-5 strokes or notches along the edge of standing stones was in use mainly from the 5thto the 7th centuries, but its use never fully died out. Of the c. 400 known Ogam inscriptions, around 330 are found in Ireland, the others are found in Britain. This article describes the writing system and the rather monotonous content – namely personal names – of the Ogam texts, as well as the language as far as it is accessible through these texts.